2016
DOI: 10.21659/rupkatha.v8n3.28
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Students and Parents on the Use of Corporal Punishment at Schools in India

Abstract: Violence against children is continuing in schools across India in spite of the strict laws against the use of Corporal Punishment (CP) at schools. The purpose of this study is to identify the reasons for the perpetration of corporal punishments at a random selection of Indian schools as experienced by the students. The population of the sample is small but and the result may be indicative and at the same time may not reflect the condition in the whole of India. The study focuses on the notions of violence wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The design of MolSandbox, which allows for systematic exploration of molecular factors with explicit, written goals, may be more aligned with the studying habits of culturally Eastern/Asian students (who form the majority of the University's international student cohort), whereas the more playful, problem-solving quests in MolWorlds may appeal more to culturally Western students. Eastern education has been associated with rote learning and regimented studying, with less of an emphasis on creativity and problem-solving [80,81], a greater focus on the practical outcomes of education, e.g., high-level employment [82] and higher academic and career aspirations [83][84][85]. Societal norms around gaming may also play a role; higher play approval is typically seen amongst culturally Western parents [86,87], and may be viewed as particularly distracting or academically damaging in culturally South-Asian households [85].…”
Section: Moderating Effect Of Native Language-a Proxy For Culture?mentioning
confidence: 99%
See 1 more Smart Citation
“…The design of MolSandbox, which allows for systematic exploration of molecular factors with explicit, written goals, may be more aligned with the studying habits of culturally Eastern/Asian students (who form the majority of the University's international student cohort), whereas the more playful, problem-solving quests in MolWorlds may appeal more to culturally Western students. Eastern education has been associated with rote learning and regimented studying, with less of an emphasis on creativity and problem-solving [80,81], a greater focus on the practical outcomes of education, e.g., high-level employment [82] and higher academic and career aspirations [83][84][85]. Societal norms around gaming may also play a role; higher play approval is typically seen amongst culturally Western parents [86,87], and may be viewed as particularly distracting or academically damaging in culturally South-Asian households [85].…”
Section: Moderating Effect Of Native Language-a Proxy For Culture?mentioning
confidence: 99%
“…Eastern education has been associated with rote learning and regimented studying, with less of an emphasis on creativity and problem-solving [80,81], a greater focus on the practical outcomes of education, e.g., high-level employment [82] and higher academic and career aspirations [83][84][85]. Societal norms around gaming may also play a role; higher play approval is typically seen amongst culturally Western parents [86,87], and may be viewed as particularly distracting or academically damaging in culturally South-Asian households [85]. This argument sup-ports the concept that learning technologies which incorporate entertainment elements and have more of a playful, problem-solving focus may be perceived as more acceptable and effective for Western learners, whereas more structured investigation and experimentation may be more appealing for learners who identify with Eastern cultures.…”
Section: Moderating Effect Of Native Language-a Proxy For Culture?mentioning
confidence: 99%
“…A study by Agrasar (2018) argues that several episodes of corporal punishment are not reported primarily because of social norms and attitudes towards the use of punishment in India. There is a likelihood that teachers in India may have veered toward the use of reactive strategies to address socially unacceptable behaviour (Agrasar, 2018; Ghosh & Pasupati, 2016) and may even continue to believe that students are punished for their benefit (Agrasar, 2018; Cheruvalath & Tripathi, 2015). Historically, in Indian society, teachers are often seen as authoritative figures in children’s lives and with that authoritative status (Raj, 2011) they are in a position to use any behaviour management strategy they feel is appropriate for the student (Agrasar, 2018; Tiwari, 2014).…”
mentioning
confidence: 99%